2006
DOI: 10.1089/ten.2006.12.2825
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant Functionality in Hepatocytes Using the Enhanced Collagen Extracellular Matrix Under Different Oxygen Tensions

Abstract: Improvement of O(2) supply in bioartificial liver devices remains a critical issue in maintaining hepatocyte viability and functions. Therefore, the current study investigates whether enhanced oxygen (O(2)) transport through collagen extracellular matrix (ECM) can produce a more stable antioxidant defense in different O(2) tensions during prolonged incubation times. Total glutathione concentration of cultured hepatocytes in enhanced ECM was significantly higher than in normal ECM under the lowest O(2) tension … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 32 publications
0
4
0
1
Order By: Relevance
“…[2,7,8] In the absence of a vascular supply, the transport of nutrients occurs mainly by diffusion, a transport mechanism that is only efficient over short distances or for tissues with low metabolic activity (e.g., cartilage). Theoretical modeling predicts [2] that a centimeter thick scaffold without a vascular supply can support the metabolism of 280 000 cells Á cm À3 without central necrosis; in native cancelous bone, this value is 1000-fold higher.…”
mentioning
confidence: 99%
“…[2,7,8] In the absence of a vascular supply, the transport of nutrients occurs mainly by diffusion, a transport mechanism that is only efficient over short distances or for tissues with low metabolic activity (e.g., cartilage). Theoretical modeling predicts [2] that a centimeter thick scaffold without a vascular supply can support the metabolism of 280 000 cells Á cm À3 without central necrosis; in native cancelous bone, this value is 1000-fold higher.…”
mentioning
confidence: 99%
“…Concomitant blood vessels play a vital role in supplying oxygen and nutrients to newly formed tissues, eliminating metabolites, delivering growth factors and providing key signals for bone metabolism [30]. Insufficient early angiogenesis will hinder the biomaterial fusion and absorption with tissues, and then hindering the bone regeneration [12,13]. Some studies have demonstrated the effect of BG on promoting angiogenesis [31][32][33], but the early proangiogenic capacity of BG, especially the early angiogenesis in large-sized bone defects filled with BG, needs more studies [9][10][11].…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, some literatures also pointed out that acute inflammatory reactions will occur when biomaterials are implanted, which will inhibit the angiogenesis process of osteoblasts and epithelial cells [10,11]. The inadequate early angiogenesis of BG may result in insufficient nutrient supplies and harmful microenvironment changes, which weakens its osteogenic effects in large-sized bone defects repair, leading to ischemia and tissue necrosis in the central region of bone defects or ultimately the failure of bone regeneration [12,13]. Therefore, inadequate angiogenesis is a problem that has created a bottleneck in tissue engineering.…”
Section: Introductionmentioning
confidence: 99%
“…Снабжение кислородом является лимитирующим фактором при культивировании активно метаболизирующих клеток, таких как гепатоциты [9][10][11]. Nahmias и соавт.…”
Section: подбор средunclassified